Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Kepuasan Anggota Terhadap Pengguna Jasa di KSP Kopdit Swasti Sari Cabang Atambua - Cecilia Novianti Salsinha; Yovita Alves Amsikan; Eva Binsasi (Journal of Science and Technology, 2022)
The lack of employees at KSP Kopdit Swasti Sari Atambua branch where often employees in the finance department (tellers) concurrently serve as customer service and very few employees in the credit staff so that the survey of the borrower's location is delayed. Loans and loan interest rates are often compared to other cooperatives so that these cooperatives are required to compete with other cooperatives or business entities. Experienced several office location changes. The purpose of this study was to determine the effect of service quality, product quality and company image on member satisfaction. The population of this study were all members of KSP Kopdit Swasti Sari Atambua branch, totaling 3,707 people with a sample of 98 people. The data collection instrument used a questionnaire. The data analysis method used is multiple linear regression. The results of this study indicate that product quality and company image variables affect member satisfaction by 22.7%. The multiple linear regression equation is obtained Y=25,233+0,333X2+0,197X3